THE USE OF LOCAL VARIETY OF ENGLISH IN THE CONTEXT OF INTERNATIONAL COMMUNICATION - Muth’im, Abdul (Vidya Karya Jurnal Kependidikan, 2014)
At the early periods of Indonesian education, learning English was usually understood as learning either American English or British English with all its specific features and characteristics. For the purpose of acquiring such kind of English, many Indonesian students were sent to either one of the countries by our government or native English teachers/ lecturers of those countries were invited to Indonesia to teach Indonesian learners English. This might be based on the belief that the English used in both countries is considered standard. It was believed then that only students who had acquired standardized English well that would be able to engage in international communication well. As time goes by, however, sending students to English speaking countries to learn English or inviting native English teachers/lecturers to teach Indonesian students English is considered ineffective and inefficient anymore. In addition, the policy of Indonesian government in the field of education stipulates that English is the first foreign language that should be learned by Indonesian students. As a result, the number of Indonesian students learning English is getting more and more in every academic school year. The consequence of this shift of policy necessitates Indonesian government to run the program of teaching and learning English domestically with domestic English teachers. The change of policy, of course, gives impact to the result of English learning. Studentsâ cultural and language background as well as teachersâ/lecturersâ cultural and language background must contribute to the English yielded. The impact is the English used is inevitably influenced by Indonesian English teachers and Indonesian English learners. In other words, the English produced is not American English nor British English, but a local variety of English, Indonesian-English. This paper tries to explore and discuss the role of local variety of English as medium of communication in international context.